2016
DOI: 10.1073/pnas.1510502113
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing treatment pathways at scale using the OHDSI network

Abstract: Observational research promises to complement experimental research by providing large, diverse populations that would be infeasible for an experiment. Observational research can test its own clinical hypotheses, and observational studies also can contribute to the design of experiments and inform the generalizability of experimental research. Understanding the diversity of populations and the variance in care is one component. In this study, the Observational Health Data Sciences and Informatics (OHDSI) colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
222
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 285 publications
(231 citation statements)
references
References 38 publications
(25 reference statements)
5
222
0
Order By: Relevance
“…21 Big Data provides an opportunity for personalized care for everyone and may be used in precision medicine to optimize treatment for individual patients. 22,23 It has the potential to especially benefit racial-ethnic minority and other underserved populations for whom we do not have evidence, because most clinical trial data were analyzed without adequate numbers of minority or low SES populations. 24 With the adoption of EHRs in all health care settings, and the incorporation of additional digital health information from monitoring, big clinical data will be generated and available to provide the means for conducting pragmatic trials including underserved populations and to help compensate for the lack of disparity populations in randomized clinical trials.…”
Section: Opportunity I: To Incorporate Social Determinants Informatiomentioning
confidence: 99%
“…21 Big Data provides an opportunity for personalized care for everyone and may be used in precision medicine to optimize treatment for individual patients. 22,23 It has the potential to especially benefit racial-ethnic minority and other underserved populations for whom we do not have evidence, because most clinical trial data were analyzed without adequate numbers of minority or low SES populations. 24 With the adoption of EHRs in all health care settings, and the incorporation of additional digital health information from monitoring, big clinical data will be generated and available to provide the means for conducting pragmatic trials including underserved populations and to help compensate for the lack of disparity populations in randomized clinical trials.…”
Section: Opportunity I: To Incorporate Social Determinants Informatiomentioning
confidence: 99%
“…10,17 The pathway systems could become a driver of change in clinical practice in the US and around the world, influencing both the patient and provider side of healthcare. In addition, clinical pathways can serve as a framework for moving forward and increasing the efficiency of care while decreasing the variation in care.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent study by Hripcsak et al characterized treatment pathways on a global scale and found that the pathways improved consistency of therapy across diseases and locations. 10 In 2012, University of Pittsburgh Medical Center (UPMC) introduced a hysterectomy clinical pathway to reduce the number of total abdominal hysterectomies being performed for benign gynecological indications. 4,11 We hypothesized that pathways could be a unifying vehicle of change for both providers and patients in choosing the most optimal surgical approach to hysterectomy, which can have very important implications for gynecologic care and healthcare in general.…”
mentioning
confidence: 99%
“…For example, Hripcsak et al used OHDSI to combine data from 11 data sources, a total of 250 million patients, to examine treatment pathways in type 2 diabetes mellitus, hypertension and depression [8]. Substantial R&D investments are currently being made to develop tools, platforms and governance processes to enable the distributed analysis of multiple EHR systems [9,10].…”
Section: Introductionmentioning
confidence: 99%